Faktor-Faktor Penyebab Kesulitan Membaca Permulaan di Kelas 1 SD Negeri Sampangan 02 - Arief Syaiful Rachman; Iin Purnamasari; Sukamto Sukamto; Puput Sulistyowati Lestari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to find out what factors hinder students from having difficulty with beginning reading and solutions to overcome the problems of students with initial reading difficulties in grade 1B of SD Negeri Sampangan 02. The type of research used is descriptive qualitative research. Collecting data in this study is by observation method using guiding indicators to determine the difficulty of beginning reading, interviews, and documentation. The instrument used was a non-test instrument in the form of a questionnaire regarding initial reading difficulties. After the researcher received the data, the data was analyzed using the Milles and Huberman model. The results of this study show 1. the causative factors of early reading difficulties are lazy learning, lack of interest and motivation to learn, power, students get bored easily, lack of parental guidance and attention to education. 2. The solution for beginning reading difficulties is that the teacher provides additional hours for students learning to read beginning, paying special attention to students who have difficulty reading beginning, parental concern for their child's education, the teacher must be creative when guiding students learning to read beginning.